Validation of the Korean Frailty Index in community-dwelling older adults in a nationwide Korean Frailty and Aging Cohort study - Hee-Won Jung; Sunyoung Kim; Chang Won Won (The Korean Journal of Internal Medicine, 2021)
Background/Aims We aimed to assess validity of the Korean Frailty Index (KFI) and the modified KFI (mKFI) in nationwide Korean population as screening measures for frailty status in older adults. Methods Analysis was performed in the records of baseline assessments of 2,886 participants in the Korean Frailty Aging Cohort study from 2016 to 2017. The KFI included eight items on a history of hospitalization, self-reported health status, polypharmacy, weight loss, mood, incontinence, sensory problems, and timed up and go test. In mKFI, timed up and go test was replaced with a question whether a person can walk around a schoolyard. Cardiovascular Health Study (CHS) frailty scale was used as a gold standard. Results In study population (mean age, 76; 47.6% men), score of the KFI correlated with the CHS scale. The KFI correlated with common geriatric parameters including Activities of Daily Living, nutritional status, cognitive performance, and mood. As a construct validity, items of KFI correlated with CHS scale. As a criterion validity, sensitivity was 81.6%, specificity was 67.0% to predict frailty by CHS scale with the score of 3 or higher in KFI. The KFI and mKFI correlated with each other (R2 = 0.88), and prediction ability for frailty by CHS scale was not significantly differed between KFI and mKFI. Conclusions The KFI and mKFI are valid instruments for frailty screening and might be useful as simple frailty screening tools to identify older adults who might benefit from comprehensive geriatric assessment and integrated, multidisciplinary geriatric care services.